2010
DOI: 10.1007/s00603-010-0100-y
|View full text |Cite
|
Sign up to set email alerts
|

Sheeting Joints: Characterisation, Shear Strength and Engineering

Abstract: Sheeting joints are extensive fractures that typically develop parallel to natural slopes. Embryonic sheeting joints initially constitute channels for water flow and then become the focus for weathering and sediment infill accompanied by progressive deterioration and dilation. Slabs of rock fail along them periodically because of their adverse orientation and long persistence. They are however rough and wavy and these characteristics contribute highly to their shear strength and improve their stability. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…Targetlike ores can develop once the very late exhumation of the peridotite massif and its erosion has induced mechanical decompression and subsequent jointing. The bulk permeability of the first hundreds of meters below the surface is thus increased by this process (Hencher et al 2011). The high permeability of the saprocks allows rapid vertical transfer and short residence time for the incoming waters.…”
Section: Discussionmentioning
confidence: 99%
“…Targetlike ores can develop once the very late exhumation of the peridotite massif and its erosion has induced mechanical decompression and subsequent jointing. The bulk permeability of the first hundreds of meters below the surface is thus increased by this process (Hencher et al 2011). The high permeability of the saprocks allows rapid vertical transfer and short residence time for the incoming waters.…”
Section: Discussionmentioning
confidence: 99%
“…41-42) explains that the higher the value of Poisson's ratio for a given material, the higher the gravitationally-induced horizontal stresses for any given vertical stress. The density of pre-existing joints influences the development of sheeting joints because the pre-existing joints accommodate the relief of stresses (Hencher et al, 2011), as such sheeting joints are rarely found in intenselyjointed granite for example (Twidale, 1973). Further, at individual sites within uniform rock masses, the development of sheeting joints will be spatially variable because of variation in stress redistribution.…”
Section: Rock Stress Redistributions and Jointingmentioning
confidence: 99%
“…While several mechanisms have been proposed to explain the formation of these joints, including the mechanical effects of fire, thermal cycles, vegetation and chemical weathering, it has generally been accepted that they are generated by gravitational stresses and usually triggered by unloading (Brunner and Scheidegger, 1973). (Hencher et al, 2011). The high horizontal to vertical stress ratios, σ h /σ v , and the development of joints parallel to the land surface indicate that failure may have been induced by compressive stresses (i.e.…”
Section: Rock Stress Redistributions and Jointingmentioning
confidence: 99%
See 1 more Smart Citation
“…The failure was the final stage of a progressive landslide that had been developing over many years involving dilation during rainstorms, the extension of proto-joints and development of new fractures and the intermediate washing in of sediments to apertures (Hencher et al 2011). In the failed area, major waves on the sheeting joints had a wavelength of about 2 m and amplitude of about 0.15 m. Following the failure, roughness was measured using compass clinometers on 80 and 420 mm plates using a 0.1 m grid pattern in areas where the slope had failed and in areas that had not failed.…”
Section: Roughness and Scale Effectsmentioning
confidence: 98%